Civic Education Based IT Management at SMKN 2 Purbalingga - Listyorinie, Listyorinie (2012)
This research are to describe (1) the classroom setting characteristic of IT-Based Civic Education Learning at SMK Negeri 2 Purbalingga; (2) the material characteristics of IT-Based Civic Education Learning at SMK Negeri 2 Purbalingga; (3) the interaction characteristics of IT-Based Education Learning at SMK Negeri 2 Purbalingga. This research is a qualitative research using the ethnography design. This research was conducted in SMK Negeri 2 Purbalingga. The resource persons in this research were the Principal, teachers, and students. Data collection methods used was depth interviews, observations, and documentations. Data analysis used was the analysis technique arranged in a site. The results of the research shows; (1) the classroom settings that are used in IT-based Civic Education learning are in classical form and in groups. The characteristics are the classroom lighting not too bright, comfortable for students to see the results of an LCD display, tables and chairs face the LCD screen, and pay attention to the current source to be used. The principle used in the determination of classroom setting is the effectiveness of media, the efficiency of learning time, and convenience; (2) The materials of IT-based Civic Education have the higher difficulty level than other materials. The materials are presented to simplify the way of students' thinking in understanding Civic education and the higher complexity materials become simple and easy to be understood and implemented. The materials can be developed by students with using internet as the learning source. The materials are also presented in the teachers' private blogs that can be accessed by students. The assignments are sent via email. The materials are presented through the LCD media in the form of pictures, graphics, data, maps, diagrams, exposure or power point, and in film in accordance with the learning materials; (3) teachers interact directly with students by explaining materials. The teachers explain the learning materials with LCD. Students interact directly with other students in group discussions and they have their own working system. Teachers and students interact indirectly via Internet. Students send the assignments via email and the teachers give confirmation by giving answer via email.